#TITLE_ALTERNATIVE# - WAHYU ROMADHONIA (NIM: 10311019); Pembimbing : Dr. rer. nat. M. Ikbal Arifyanto, RISKA
The structure of embedded clusters is an important clues to study the star formation process and its evolution. There are three types of cluster structure, uniform distributed clusters, radially concentrated clusters, and a fractal subclustering. Parameter Q is widely used for the analyzing the structure of embedded clusters. An additional reducing operation needed to give a better understanding of substructure. In this work, we used three embedded clusters, which are NGC 2264, NGC 6334, and RCW 36. Parameter Q calculation shows that NGC 2264 and NGC 6334 is a fractal clusters (Q < 0:8), and RCW 36 is concentrated cluster (Q > 0:8). The substructure in MST graph also observed in a previous study by Kuhn et al. (2014). Kuhn et al. (2014) identify substructure of embedded clusters using the smoothed projected stellar surface density. Based on the pattern of substructure, RCW 36 has dynamically evolved much more than NGC 2264 and NGC 6334, even though RCW 36 was the youngest cluster among them.